Which sectors of the Icelandic economy are likely to benefit the most after the Free Trade Agreement with China? - Hugo Miguel Borges Esteves 1977- (2014)
This thesis analyses which sectors of the Icelandic economy are likely to benefit the most after the Free Trade Agreement (FTA) with China. The fishing industry, the service sector and the manufacturing sector are very likely to benefit. Other sectors can also be affected in a positive way, especially agriculture. How the FTA will impact the different sectors of the Icelandic economy is very interesting because once it enters into force, tariffs on most goods will disappear. In order to analyse which sectors of the Icelandic economy are likely to benefit after the FTA, qualitative and quantitative research methods were used. Össur Skarphéðinsson, the Minister of foreign affairs who signed the agreement, was interviewed in depth. The nummerical data examined was helpful to see the business trend between the two countries in the last years. In addition, these numbers give a good insight about what is about to come and, thus, reveal interesting facts. Since Iceland mainly exports fish to China, the fishing industry is very liklely to make tremendous gains in the first years. Icelandic fish and fish products will become cheaper and more competitive in the Chinese market. Medium-term, the service sector can achieve significant gains with turism, and if a port is built in Iceland to service ships travelling the Northern Sea Route. Competitive Icelandic manufacturing companies could also gain a foothold in China. Even though it is just a long shot, it is possible that Iceland can export oil to China if this commodity is found in the Dreki-area. This would surely boost Icelandic economy in the future.